2019
DOI: 10.1111/mpp.12768
|View full text |Cite
|
Sign up to set email alerts
|

Two venom allergen‐like proteins, HaVAP1 and HaVAP2, are involved in the parasitism of Heterodera avenae

Abstract: Summary Despite the fact that venom allergen‐like proteins (VAPs) have been identified in many animal‐ and plant‐parasitic nematodes, studies on VAPs in Heterodera avenae , which is an important phytonematode, are still in their infancy. Here, we isolated, cloned and characterized two VAP s, named HaVAP1 and HaVAP2 , from H. avenae . The two encoded proteins, HaVAP1 and HaVAP2, harbour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Importantly, VAPs are key players in the modulation of plant immunity. Knocking down the expression of VAP genes can severely affect nematode virulence [ 45 , 56 , 57 , 58 ]. In particular, expression of VAP genes are required for the onset of parasitism at the time of root invasion and migration through host tissues [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, VAPs are key players in the modulation of plant immunity. Knocking down the expression of VAP genes can severely affect nematode virulence [ 45 , 56 , 57 , 58 ]. In particular, expression of VAP genes are required for the onset of parasitism at the time of root invasion and migration through host tissues [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, A. thaliana lines overexpressing nematode VAP genes loose basal immunity to unrelated pathogens, including fungi, bacteria, and oomycetes [ 46 ]. Modulation of plant immunity involves interaction of nematode VAPs with host proteases [ 45 , 57 ]. In tomato, Gr-VAP1 specifically interacts with and inhibits the apoplastic papain-like cysteine protease (PLPC) Rcr3pim, increasing the susceptibility of tomato plants to G. rostochiensis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate BiFC constructs, the full-length cDNA of AopN was cloned into a pSPYNE ® 173 vector [ 44 ], and the full-length cDNA of ClHIPP and ClLTP was cloned into the pSPYCE (M) vector [ 44 ]. The constructs were co-expressed in N. benthamiana leaves for analysis, as previously described [ 44 , 45 ]. After 48 h, at an excitation wavelength of 488 nm to acquire fluorescent images, the plasma membrane marker dye (Dil, D3911, Thermo Scientific, Waltham, MA, USA) was used as the control for PM localization.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the transient expression of Ha-annexin led to the down-regulation of the host hypersensitive (HR) response induced by BAX protein and different pathogen associated molecular patterns (PAMPs) such as flagellin [100]. Very recently two venom allergen-like effector proteins (HaVAP1 and HaVAP2) from H. avenae have been characterized through gene silencing [101]. The results indicated that both of them are involved in the suppression of programmed cell death induced by BAX in Nicotiana benthamiana leaves.…”
Section: Nematode Resistance Through Modern Approachesmentioning
confidence: 99%